3D characterization of internal defects for fatigue performance of welded SA192 steel water walls. (April 2023) - Dev Choudhury, Suvan; Li, Leijun; Saini, Nitin; Khan, Waris Nawaz; Ravikiran, K.; Lyu, Zhe
Abstract: Weld defects in SA192 steel water walls have been characterized using 3D nano-tomography. The fatigue test specimens were extracted from different weld locations of the water walls. The internal welding defects number, size, shape, and location were measured before low-cycle fatigue tests. The weld defect size and shape were found to be the most prominent factors influencing fatigue crack initiation and fatigue life. Sharper defects significantly reduce the fatigue life of the specimen as compared to the rounder defects. The stress intensity factor for each type of defects was calculated using linear-elastic fracture mechanics and the Murakami methods. In the defect-free specimens, the weld fusion zone was the most preferential sites for fatigue crack initiation due to a higher hardness of the as-solidified microstructure. Highlights: Correlation of internal defects with fatigue life of service aged water walls. 3D investigation for comprehensive characterization of internal defects. Effect of defect shape, size, and position on fatigue crack initiation and growth. Calculation and comparative assessment of stress intensity factor using LEFM and Murakami methods.